2008
DOI: 10.1002/arch.20219
|View full text |Cite
|
Sign up to set email alerts
|

Bracovirus gene products are highly divergent from insect proteins

Abstract: Recently, several polydnavirus (PDV) genomes have been completely sequenced. The dsDNA circles enclosed in virus particles and injected by wasps into caterpillars appear to mainly encode virulence factors potentially involved in altering host immunity and/or development, thereby allowing the survival of the parasitoid larvae within the host tissues. Parasitoid wasps generally inject virulence factors produced in the venom gland. As PDV genomes are inherited vertically by wasps through a proviral form, wasp vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Indeed, a recent high through-put transcriptomic analysis confirmed the prediction that a majority of CcBV genes possess at least one intron and also revealed that they harbour arthropod transcription start sites and exhibit GC contents similar to wasp genes -in contrast to the nudivirus genes that do not contain introns and are slightly more AT-rich [21 ]. Despite these structural similarities, the formal demonstration of gene transfer between insects and BVs is in most cases difficult to obtain because of divergence of BV sequences with the original insect genes [37]. Ancient gene transfers (86 million years ago) occurring very early in the history of the BV-wasp associations are, for example, probably at the origin of the Ankyrin and PTP BV gene families, as no clear phylogenetic link can be established with corresponding insect genes [22,36,38] and as they are shared by nearly all BVs (except Chelonus inanitus BV).…”
Section: Origin Of Genes Encoded By Bv Segmentssupporting
confidence: 52%
“…Indeed, a recent high through-put transcriptomic analysis confirmed the prediction that a majority of CcBV genes possess at least one intron and also revealed that they harbour arthropod transcription start sites and exhibit GC contents similar to wasp genes -in contrast to the nudivirus genes that do not contain introns and are slightly more AT-rich [21 ]. Despite these structural similarities, the formal demonstration of gene transfer between insects and BVs is in most cases difficult to obtain because of divergence of BV sequences with the original insect genes [37]. Ancient gene transfers (86 million years ago) occurring very early in the history of the BV-wasp associations are, for example, probably at the origin of the Ankyrin and PTP BV gene families, as no clear phylogenetic link can be established with corresponding insect genes [22,36,38] and as they are shared by nearly all BVs (except Chelonus inanitus BV).…”
Section: Origin Of Genes Encoded By Bv Segmentssupporting
confidence: 52%
“…Three of these new genes could be mapped to the integrated genome (CcBV_3.9, CcBV_20.6, and CcBV_28. 22), whereas the remaining four genes (bv3-4, bv5-9, bv7-8, and ep1-like7) belonged to known BV multigenic families but were not present in the integrated or packaged genome previously sequenced, suggesting that either certain segments were not perfectly assembled or a few proviral segments remain unidentified. Organization of CcBV genes expressed in immune tissues.…”
Section: Global Transcriptome Statistics Obtained From Nonparasitizedmentioning
confidence: 96%
“…However, phylogenetic analyses suggesting viral genes could be of hymenopteran origin have so far been performed for only a few genes (20). Indeed, most genes appear to have diverged considerably in their sequence from insect genes (22). The encapsidated genomes of BVs from closely related wasps share many conserved genes (20), whereas distantly related wasps share very few genes (17).…”
Section: Importancementioning
confidence: 99%
“…However, no PDV-possessing DNA polymerase has been identified since its gene is not likely to be encapsulated in viral particles (32). Current approaches for identifying PDV genomes using ovarian EST or analysis of BAC clones containing PDV segments clearly suggest that viral coat protein genes, which are not encapsulated, are actively expressed during viral replication (33,34). Viral DNA amplification during replication has not been observed for PDVs.…”
Section: Discussionmentioning
confidence: 99%